Growth and productivity of purging nut (Jatropha Curcas L.) crop grown on an Oxisol in tangará da serra (MT, Brasil) - Dalchiavon, F. C. [UNESP]; Dallacort, R.; Colleti, A. J.; Montanari, R. [UNESP]; Paz-Ferreiro, J. (My University, 2013)
The purging nut (Jatropha. Curcas, L.) is a flowering plant, described as a poisonous, semi-evergreen shrub or small tree, which belongs to the family Euphorbiaceae. Cultivation is uncomplicated and the plant shows a fast vegetative growth, so that the reproductive period is achieved within six months. In Brazil, research dealing with this crop is rather recent so that there is a need to farther assess adequate management of this species. Therefore, the aim of this work was to evaluate growth and productivity of a purging nut crop growing on an Oxisol (Latossolo Vermelho Distroférrico following the Brazilian Soil Classification System) at the Tangará da Serra municipality, MT, Brazil. The field work was performed from August 2007 to August 2008 at the experimental site of Universidade do Estado de Mato Grosso (UNEMAT), located at 14°37'10 south latitude and 57°29'09 west longitude and with 320 mean altitude asl. Plant height and plant production of purging nut were determined. Mean productivity per hectare and per plant during the first year of cultivation as the sum of all the values of the respective individual determinations. Mean growth of purging nut plants during the studied period was 148.45 cm, corresponding to 0.56 cm day-1. Most seed production occurred during the third productive month, which accounted for 44.51% of the total. The mean final productivity was as high as 595.36 kg ha-1 of seeds.
Keywords: Jatropha curcas l.; Oxisol; Phenological stages; Seed production